A Surface Exposed, Two-Domain Lipoprotein Cargo of a Type XI Secretion System Promotes Colonization of Host Intestinal Epithelia Expressing Glycans - Grossman, Alex S.; Escobar, Cristian A.; Mans, Erin J.; Mucci, Nicholas C.; Mauer, Terra J.; Jones, Katarina A.; Moore, Cameron C.; Abraham, Paul E.; Hettich, Robert L.; Schneider, Liesel; Campagna, Shawn R.; Forest, Katrina T.; et al. (Frontiers in Microbiology, 2022)
The only known required component of the newly-described Type XI secretion system (TXISS) is an outer membrane protein (OMP) of the DUF560 family. TXISSOMPs are broadly distributed across proteobacteria, but properties of the cargo proteins they secrete are largely unexplored. We report biophysical, histochemical, and phenotypic evidence that Xenorhabdus nematophila NilC is surface-exposed. Biophysical data and structure predictions indicate that NilC is a two-domain protein with a C-terminal, 8-stranded β-barrel. This structure has been noted as a common feature of TXISS effectors and may be important for interactions with the TXISSOMP. The NilC N-terminal domain is more enigmatic, but our combined results indicate it to be ordered and to contain β−sheet, and bioinformatics suggest structural similarities to carbohydrate binding proteins. X. nematophila NilC and its presumptive TXISSOMP partner NilB are each required for colonizing the anterior intestine of Steinernema carpocapsae nematodes: the receptacle of infective stage juveniles and the anterior intestinal caecum (AIC) in juveniles and adults. The former contains a mucus that interacts with wheat-germ-agglutinin (WGA). We show that in adult nematodes the AIC expresses a WGA-reactive material, indicating the presence of N-acetylglucosamine or N-acetylneuraminic acid sugars on the AIC surface. A role for this material in colonization is supported by the fact that exogenous addition of WGA can inhibit AIC colonization by X. nematophila. Conversely, the addition of excess, purified NilC increases the frequency with which X. nematophila is observed at the AIC, demonstrating that abundant extracellular NilC can enhance colonization. NilC may facilitate X. nematophila adherence to the nematode intestinal surface by binding to host glycans, it might support X. nematophila nutrition by cleaving sugars from the host surface, or it might play a glycan-independent role such as protecting X. nematophila from nematode host immunity. Proteomic and metabolomic analyses of wild type X. nematophila compared to those lacking nilB and nilC revealed differences in cell wall and secreted polysaccharide metabolic pathways. Overall, these findings support a model that NilB-regulated surface exposure of NilC mediates interactions between X. nematophila and host surface glycans during colonization. This is a previously unknown function for a TXISS.